2011
DOI: 10.1186/1471-2180-11-157
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effect of Lactobacillus strains against gas-producing coliforms isolated from colicky infants

Abstract: BackgroundInfantile colic is a common disturb within the first 3 months of life, nevertheless the pathogenesis is incompletely understood and treatment remains an open issue. Intestinal gas production is thought to be one of the causes of abdominal discomfort in infants suffering from colic. However, data about the role of the amount of gas produced by infants' colonic microbiota and the correlation with the onset of colic symptoms are scanty. The benefit of supplementation with lactobacilli been recently repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 27 publications
7
73
0
2
Order By: Relevance
“…The clinical significance of this is now recognized by its association with nosocomial infections in cohorts of hospitalized patients, including children and neonates. [8][9][10] KPC-producing K. pneumoniae are responsible for higher mortality as compared to non-KPC producers. 11 We observed three isolates of K. pneumoniae that were resistant to colistin and 10 isolates showed resistance to tigecyclin, while none of K. oxytoca showed any resistance to these two antibiotics.…”
Section: S60 Discussionmentioning
confidence: 99%
“…The clinical significance of this is now recognized by its association with nosocomial infections in cohorts of hospitalized patients, including children and neonates. [8][9][10] KPC-producing K. pneumoniae are responsible for higher mortality as compared to non-KPC producers. 11 We observed three isolates of K. pneumoniae that were resistant to colistin and 10 isolates showed resistance to tigecyclin, while none of K. oxytoca showed any resistance to these two antibiotics.…”
Section: S60 Discussionmentioning
confidence: 99%
“…Growing evidence underlines the fact that infantile colic can be linked to the composition of the gut microbiota, and preliminary in vitro studies have underlined the antagonistic effect of selected Lactobacillus and Bifidobacterium strains against coliforms (25,26). Clinical studies have focused mostly on the efficacy of Lactobacillus reuteri, which seemed useful for the treatment of breastfed infants suffering from infantile colic (16,(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…against a wide range of foodborne pathogens [29,30] In the present study, atypical EPEC was the only DEC category identified and isolated exclusively in the infants group who did not assume probiotics. Indeed, atypical EPEC is now predominant in industrial countries, while typical EPEC is more frequently isolated in developing areas [31].…”
Section: Recent Studies Involving the Use Of Culture-independent Techmentioning
confidence: 48%
“…In conclusion, one of the important functions of probiotics is their ability to inhibit the growth of different types of foodborne pathogens [30]; our study indicated that early administration of L.…”
Section: Discussionmentioning
confidence: 65%